Pemanfaatan Limbah Kulit Bawang Merah Menjadi Pestisida Alami Sebagai Substitusi Pestisida Kimia Di Desa Mungkung, Nganjuk - Hendra Maulana; Rafli Aprilian Firmansyah; Mochammad Rayhan Faujan; Figo Afriansyah; Hana Safira Hidayat; Herlin Dwi Dita Tamtamalia; Ghea Lintang Samputri (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
In Mungkung Village, Rejoso District, Nganjuk Regency, KKNT students at the East Java "Veteran" National Development University conducted research to use onion skin waste as raw material for making natural pesticides. The main goal is to reduce people's dependence on chemical pesticides which have negative impacts on health and the environment. The research process was carried out through observation, socialization and demonstration. The results of the activity show that natural pesticides from onion skin waste are effective in controlling plant pests and are safe for the environment because they do not leave dangerous residues. The success of this outreach and demonstration increased public awareness of the importance of using agricultural waste wisely. This activity supports the Sustainable Development Goals (SDGs), especially in responsible consumption and production as well as protecting life on land, by reducing the use of chemical pesticides and utilizing organic waste. It is hoped that this waste management model can be widely adopted for more environmentally friendly and efficient agriculture.